Deletions in the 3′ Part of the NFIX Gene Including a Recurrent Alu‐Mediated Deletion of Exon 6 and 7 Account for Previously Unexplained Cases of Marshall–Smith Syndrome. Issue 9 (8th July 2014) - Schanze, Denny; Neubauer, Dorothée; Cormier‐Daire, Valerie; Delrue, Marie‐Ange; Dieux‐Coeslier, Anne; Hasegawa, Tomonobu; Holmberg, Eva E.; Koenig, Rainer; Krueger, Gabriele; Schanze, Ina; Seemanova, Eva; Shaw, Adam C.; et al.
<x xml:space="preserve">Abstract</x> This study demonstrates that Marshall‐Smith syndrome is consistently caused by de novo NFIX mutations. It is presented for the first time that exon deletions including a recurrent AluY‐mediated exon 6 and 7 deletion account for roughly a quarter of cases. MSS‐associated mutations lead to mutant proteins with intact DNA‐binding and dimerization domains(DNAbd, MH1), while they have various alterations of their transcriptional transactivation/repression domains (CTF/NFI). Thereby they are presumed to exert dominant negative effects. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>